THE IMPLEMENTATION OF CIPP AS EVALUATION MODEL ON TEACHING ASSISTANCE IN SD BALI BILINGUAL SCHOOL AS THE PRACTICE OF KURIKULUM MERDEKA - Wedayanthi, Luh Made Dwi; Pradnyana, Putu Beny; Adiwijaya, Pande Agus (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
This research is evaluation model research by using CIPP as the evaluation model on Teaching Assistance in SD Bali Bilingual School in Bangli Regency, Bali. The CIPP model is Context, Input, Process, and Product, this model is one of the models used frequently in educational evaluation. The implementation is used the evaluative model created by Stufflebeam. The evaluation specifications on teaching assistance at SD Bali Bilingual School in Bangli Regency which displays an average score on the context aspects in the teaching assistance program is 83% including the category good, while the input evaluation is 82% in the good category. The same is true for the process aspect, which has an 81% in the good category, and the product aspect is 80% enough category. This is consistent with research from the aspects of Context, Input, Process, and Product obtained with the good criteria. This can indicate that the Teaching Assistance program was well conducted in SD Bali Bilingual School, in Bangli Regency.